Case Report: Application of combined transplantation of multiple autologous flaps in preventing empty pelvis syndrome after radical surgery for isolated sacrococcygeal recurrence of anal canal squamous - Jiang, Xiaoling; Zhang, Lixia; Shu, Haixia; Wang, Min; Xie, Shengyan; Wang, Xiaojuan; He, Lianli (Frontiers in Surgery, 2025)
Anal canal carcinoma is a rare malignancy, accounting for less than 3% of gastrointestinal tumors. Recurrent anal canal carcinoma, which occurs in less than 1% of cases, is often accompanied by severe complications. Surgery plays a crucial role in improving patients’ quality of life and controlling systemic paraneoplastic syndromes. This article reports a case of a 52-year-old female patient with recurrent anal canal squamous cell carcinoma (pT4bN0M0, Stage IIIB) 7 months after comprehensive treatment, complicated by rectovaginal fistula (RVF) and hypercalcemia of malignancy (HCM). Following multidisciplinary team (MDT) discussions, an innovative approach combining free omental packing with gracilis myocutaneous flap was adopted for the treatment of an isolated sacrococcygeal recurrent tumor after anal canal squamous cell carcinoma surgery. A tumor mass with a maximum diameter of 12.5 cm was completely resected. Postoperative pathological examination confirmed that no cancer cells were detected in multiple biopsies of the free resection margin, achieving R0 resection. After surgery, the patient's serum calcium level and serum squamous cell carcinoma antigen (SCC) returned to normal. Meanwhile, the bilateral combined myocutaneous flaps survived completely, RVF symptoms disappeared, the patient's quality of life was significantly improved, and the survival prognosis was enhanced.